2015
DOI: 10.4103/0189-6725.160438
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tuberculosis mimicking a malignant tumour

Abstract: There has been reported increased incidence of ovarian tuberculosis in the tropics since the advent of HIV/AIDS disease. We report a case of bilateral ovarian tuberculosis associated with a single right kidney of uncertain origin in an immunocompetent 15-year-old generally healthy-looking girl. Abdominopelvic scan was equivocal about the diagnosis of the lesion as it failed to differentiate it from malignancy. Tuberculin and histopathology were necessary to confirm the diagnosis of ovarian tuberculosis. Antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In another study, Yebouet et al . presented the case of a 15-year-old girl which was similar to our patient; the difference was that, in their case, the girl had a single kidney and the diagnosis and management were more difficult because of the possibility of kidney cancer [4] . Lantheaume et al also revealed that ovarian tuberculosis can mimic the radiological, clinical, and laboratory features of ovarian cancer [8] .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In another study, Yebouet et al . presented the case of a 15-year-old girl which was similar to our patient; the difference was that, in their case, the girl had a single kidney and the diagnosis and management were more difficult because of the possibility of kidney cancer [4] . Lantheaume et al also revealed that ovarian tuberculosis can mimic the radiological, clinical, and laboratory features of ovarian cancer [8] .…”
Section: Discussionsupporting
confidence: 55%
“…Extrapulmonary tuberculosis includes about 15%–20% of all cases of tuberculosis, and abdominopelvic tuberculosis is the sixth most common form [3] . The most common spots of pelvic tuberculosis are the fallopian tubes, the cervix, the endometrium, and the ovaries, respectively [4] . This type of tuberculosis usually originates from pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Initial diagnoses of TOA or ovarian malignancy can be mistaken given the similarities in clinical, radiologic, and serum markers such as an elevated cancer antigen-125 (CA-125). 8 - 12 CA-125 is elevated in 80% of postmenopausal ovarian carcinomas. 8 However in premenopausal women, elevations in CA-125 have been noted in endometriosis, TB, and other nonneoplastic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of abdominopelvic pain, ascites, nausea, vomiting, and anorexia associated with imaging tests showing pelvic mass were reported in patients with abdominopelvic tuberculosis [ 4 , 8 11 ] and may be associated with increased serum CA-125 levels [ 4 , 8 10 ]. In these women, the association of these symptoms, imaging tests, and CA 125 levels mimicked ovarian cancer, delaying the tuberculosis diagnosis.…”
Section: Discussionmentioning
confidence: 99%